Simulation Models of Energy Cables in SPICE - Uma Balaji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Accurate modeling of cables is important to study the behavior of high frequency disturbances in power converter systems. This paper reviews and compares two popular methodologies to model energy cables – an improved per unit length parameters based model and a Laplace SPICE element based model. The two models presented take into account the frequency dependence of the parameters of the cable. A ladder network is used for this purpose in the per unit length based model. The Laplace SPICE element model is generated from from a rational function approximation for the admittance parameters that are frequency dependant. The rational function approximation is obtained using a well known vector fitting algorithm.  The time and frequency domain solutions of a two wire energy cable, obtained from the two models, agree well.